TINGKAT PENGETAHUAN DAN PERILAKU SWAMEDIKASI PADA KALANGAN REMAJA: LITERATURE REVIEW - Rusdiana Tri Septiarini; Jihan Fahiroh Nur Arifin; Retno Wulan Devitri; Riyan Satria Pranata; Ainul Ghurri (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2026)
Self-medication is the use of drugs on one’s own to treat minor health issues without needing a doctor’s prescription. This practice is often done by teenagers and is influenced by their level of knowledge as well as access to health information. This study aims to examine the relationship between knowledge levels and self-medication practices among teenagers, based on previously published research. The method used is a literature review by searching for articles through several databases such as Google Scholar, ScienceDirect, and other health journal portals. The search was done using keywords like self-medication, knowledge level, self-medication behavior, teenagers, self-medication, knowledge, and adolescent. The selected articles are publications from 2016 to 2026, available in full-text format, and meet the specified inclusion criteria. Out of the 15 articles found, 11 met the criteria for analysis. The results show that most teenagers have fairly good knowledge, but there are still some misunderstandings about dosage, side effects, and how to use antibiotics. Most studies indicate that the higher someone's level of knowledge, the better their behavior is when it comes to self-medication. Additionally, health education has been shown to help improve understanding and encourage smarter self-treatment practices. It can be concluded that knowledge plays an important role in shaping safe self-medication behavior among teenagers.